Columnar self-assembly of star-shaped luminescent oxadiazole and thiadiazole derivatives12. Issue 12 (28th March 2015) - Pathak, Suraj Kumar; Gupta, Ravindra Kumar; Nath, Subrata; Rao, D. S. Shankar; Prasad, S. Krishna; Achalkumar, Ammathnadu S.
<x xml:space="preserve">Abstract</x> Blue light emitting star-shaped oxadiazole and thiadiazoles stabilizing fluid columnar phase.